AMOEBIC LIVER ABSCESS: A REPORT OF 100 CASES - Sultan, Syed; Mohammad, Gul; Rahman, S. Jamil-ur- (Journal of Ayub Medical College Abbottabad, 1993)
ABSTRACT: 100 cases of Amoebic Liver Abscess with age ranging from 20 years to 70 years have been treated over a period of 5 years. Amoebic Liver abscess was found in 8% cases of amoebic colitis. Interesting clinical observations were, afebrile presentation in 14% and jaundice in only 9% cases. In most cases liver function tests were of no significance. Hepatic scan was useful diagnostic aid. Peritoneal rupture occurred in only five cases. Open Drainage was indicated if response to antiamoebic therapy and aspiration failed or if secondary infection SUPERVENED. As such surgical open Drainage was our main approach in these cases.